Hadith #2196 - Sunan Abi Dawud - Abdullah bin Kathir al-Dari عبد الله بن كثير الداري; Ayoub al-Sakhtiyani أيوب السختياني; Hameed bin Musa'da bin al-Mubarak حميد بن مسعدة بن المبارك; Mujahid bin Jabir مجاهد بن جبر (Sunan Abi Dawud)
Abd Yazid, the father of Rukanah and his brothers, divorced Umm Rukanah and married a woman of the tribe of Muzaynah. She went to the Prophet (ﷺ) and said: He is of no use to me except that he is as useful to me as a hair; and she took a hair from her head. So separate me from him. The Prophet (ﷺ) became furious. He called on Rukanah and his brothers. He then said to those who were sitting beside him. Do you see so-and-so who resembles Abdu Yazid in respect of so-and-so; and so-and-so who re
Grade: Hasan

Hadith #3462 - Sunan Abi Dawud - Abdullah bin Abi Najih عبد الله بن أبي نجيح; Abdullah bin Kathir al-Dari عبد الله بن كثير الداري; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; ibn Abbas; Siyar bin Salaama, Abu al-Minhal سيار بن سلامة الرياحي أبو المنهال; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I heard the Messenger of Allah, (ﷺ) say: When you enter into the inah transaction, hold the tails of oxen, are pleased with agriculture, and give up conducting jihad (struggle in the way of Allah). Allah will make disgrace prevail over you, and will not withdraw it until you return to your original religion.
Grade: Sahih